2016
DOI: 10.3389/fnbeh.2015.00332
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short-Lasting Anti-Saccade Training in Homonymous Hemianopia with and without Saccadic Adaptation

Abstract: Homonymous Visual Field Defects (HVFD) are common following stroke and can be highly debilitating for visual perception and higher level cognitive functions such as exploring visual scene or reading a text. Rehabilitation using oculomotor compensatory methods with automatic training over a short duration (~15 days) have been shown as efficient as longer voluntary training methods (>1 month). Here, we propose to evaluate and compare the effect of an original HVFD rehabilitation method based on a single 15 min v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A systematic review on multisensory stimulation did not allow a valid conclusion about the effectiveness of this intervention [ 24 ]. Another interesting approach was reported using anti-saccadic training [ 25 ].…”
Section: Part 2: Compensatory Adaptation To Visual Field Loss After Bmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on multisensory stimulation did not allow a valid conclusion about the effectiveness of this intervention [ 24 ]. Another interesting approach was reported using anti-saccadic training [ 25 ].…”
Section: Part 2: Compensatory Adaptation To Visual Field Loss After Bmentioning
confidence: 99%
“…Only few RCTs are available: It has been shown that reading scrolled text for right hemianopia was effective to improve reading speed [ 26 ]. Furthermore, reading speed increased by performing a search task in a line of words [ 22 ] and anti-saccade training [ 25 ]. Other approaches, based on clinical experience, are to help orientation on the page by use of visual and tactile aids, for example the index finger, a ruler or a slightly vertically magnifying ruler with a red guideline.…”
Section: Part 2: Compensatory Adaptation To Visual Field Loss After Bmentioning
confidence: 99%
“…In particular AV stimulation significantly increased the number (56 AV and 37 VT) and amplitude of saccades (52° AV and 44° VT). Lévy-Bencheton et al (2015) [ 54 ] Before and after study n = 14 HH (8 right, 6 left) Ischemic stroke Adults The training consisted of three different anti-saccades (AS) training: one with (adaptation) and two without (delayed shift and no shift) saccadic adaptation. Each training lasted around 15–20 min Eye movements were recorded before and after training Eye movements Mean horizontal saccadic amplitude, mean fixation duration.…”
Section: Resultsmentioning
confidence: 99%
“…Eye movements were recorded using an infrared eye tracking in 16 studies [ 26 , 43 , 44 , 46 , 47 , 49 52 , 54 , 55 , 59 62 , 64 ]. In two studies, subjects’ eye movements were recorded using a scleral search coil system [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies relating to compensatory treatments are concerned with the improvement of eye movements and scanning into the affected field (Bergsma et al., 2011; Roth et al., 2009; Aimola et al., 2014; Hazelton, Pollock, Walsh, & Brady, 2015; Jacquin‐Courtois, Bays, Salemme, Leff, & Husain, 2013; Lane, Smith, Ellison, & Schenk, 2010; Pambakian, Mannan, Hodgson, & Kennard, 2004; Kerkhoff, Münssinger, & Meier, 1994; Mazer et al., 2003; Nelles et al., 2010; Taylor, Poland, Harrison, & Stephenson, 2011; Schuett, Heywood, Kentridge, Dauner, & Zihl, 2012), as well as increased saccadic movements into the affected field (Mannan, Pambakian, & Kennard, 2010; Lévy‐Bencheton et al., 2016; Kerkhoff, Münßinger, Eberle‐strauss, & Stögerer, 1992). A number of studies have specifically reported on subjective improvements in activities of daily living following compensatory therapy, such as improvements in mobility, reading, driving, and detection of obstacles (Bergsma et al., 2011; Ong et al., 2015; Keller & Lefin‐Rank, 2010; Aimola et al., 2014; Jacquin‐Courtois et al., 2013; Kerkhoff et al., 1994; Mazer et al., 2003; de Haan, Melis‐Dankers, Brouwer, Tucha, & Heutink, 2015; Hayes, Chen, Clarke, & Thompson, 2012; Nelles et al., 2001; Rowe, Conroy, et al., 2016).…”
Section: Resultsmentioning
confidence: 99%